(untitled) (Current Horticulture, 2024)
An experiment was conducted at University of Horticultural Sciences, Bagalkot, Karnataka, during Kharif 2016 and 2017 to study effect of ajwain (Trachyspermum ammi L.) varieties and nitrogen levels on its plant growth and yield attributes in semi-arid tropics of Northern Karnataka. The experiment was laid out in a split plot design with three replications by keeping varieties in main plots (Ajmer Ajwain 1, Ajmer Ajwain 93, Lam Selection 1, Lam Selection 2 and Local cultivar) and nitrogen levels in sub plots (50, 75, 100 and 125 kg/ha). The growth and yield attributes were significantly higher in improved varieties compared to local cultivar. Ajmer Ajwain 1 recorded highest plant height (81.82 and 80.56cm), number of secondary branches (52.36 and 50.98), plant spread (72.66 and 50.98cm), number of umbels/plant (177.15 and 171.88), number of umbellate/umbel (11.81 and 11.65), seed yield (14.44 and 14.26 q/ha, during both year, respectively), which was on a par with Lam Selection-1 (13.93 and 13.56 q/ha, respectively). Earliest 50 per cent flowering was observed in Ajmer Ajwain 93. Application of nitrogen up to 125 kg/ ha significantly increased growth and yield attributes which were on a par with 100 kg N/ha. Maximum seed yield g/plant, seed yield q/ha and essential oil yield kg/ha were recorded with 125 kg N/ha. Earliest 50 per cent flowering was observed under 50 kg N/ha application. Ajmer Ajwain1 and Lam Selection 1 were found better with an optimum dose of 100 kg N/ha.